The fish collection of José Mariano da Conceição Veloso (1742–1811) and the beginning of ichthyological research in Brazil, with a taxonomic description of the extant specimens - Ceríaco, Luis M. P.; Santos, Bruna S.; Semedo, Thiago B. F.; Garcia, Lucas Canes; Moreira, Cristiano Rangel (Zootaxa, 2023)
Two Portuguese institutions, the Museu Maynense da Academia das Ciências de Lisboa (ACL), and the Museu da Ciência da Universidade de Coimbra (MCUC), house a collection of 85 dried fish specimens prepared in what can be called a “fish-herbaria” following a process similar to that developed by the Dutch naturalist Johan Frederic Gronovius (1690–1762). These specimens date back to the late eighteenth century and represent Brazilian taxa. Previous authors assumed that they were part of the collections amassed by the Brazilian-Portuguese naturalist Alexandre Rodrigues Ferreira (1756–1815) during his “philosophical voyage” to the Amazon. Here we present a review of these specimens, suggesting that they belonged to Friar José Mariano da Conceição Veloso (1742–1811) and describe the history of dispersal of these collections up the present day. A total of 58 species in 50 genera, 32 families and 19 orders are represented in the collection. Only 8.6% of these specimens represent freshwater species, while 91.4% are marine or brackish water species. The present known distribution of these taxa is focused on southwestern Brazil, which agrees with the area where Veloso collected natural history specimens. A good percentage of the species were undescribed at the time Veloso collected them, and had they been published by him, would have had priority over species described decades later by famous eighteenth and nineteenth century ichthyologists. We also present a brief discussion on the challenges and opportunities of studying historical natural history specimens, with special focus on those amassed during the late eighteenth and early nineteenth century by Brazilian-Portuguese naturalists.